The shift in tuberculosis timing among people living with HIV in the course of antiretroviral therapy scale‐up in Malawi. Issue 4 (30th April 2019) - Tweya, Hannock; Feldacker, Caryl; Mpunga, James; Kanyerere, Henry; Heller, Tom; Ganesh, Prakash; Nkosi, Dave; Kalulu, Mike; Sinkala, George; Satumba, Thomas; Phiri, Sam
Abstract: Introduction: Although the use of antiretroviral therapy (ART) reduces HIV‐associated tuberculosis (TB), patients living with HIV receiving ART remain at a higher risk of developing TB compared to those without HIV. We investigated the incidence of TB and the proportion of HIV‐associated TB cases among patients living with HIV who are receiving ART. Methods: The study used TB registration and ART programme data collected between 2008 and 2017 from an integrated, public clinic in urban Lilongwe, Malawi. ART initiation was based on either WHO clinical staging or CD4 cell count. The CD4 thresholds for ART initiation eligibility was initially 250 cells/μL then changed to 350 cells/μL in 2011, 500 cells/μL in 2014 and to universal treatment upon diagnosis from 2016. Using TB registration data, we calculated the proportion of TB/HIV patients who were already on ART when they registered for TB treatment by year of TB registration. ART registration data were used to examine TB incidence by calendar year of ART follow‐up and by time on ART. Results: The overall proportion of TB/patients living with HIV who started TB treatment while on ART increased from 21% in 2008 to 81% in 2017 but numbers remained relatively constant at 500 TB cases annually. The overall incidence rate of TB among patients on ART was 1.35/100 person‐years (95% CI 1.28 to 1.42). The incidence of TB by time on ART decreased from 6.4/100 person‐years in the first three months of ART to 0.4/100 person‐years after eight years on ART. TB incidence was highest in the first month on ART. The annual rate of TB among patients on ART rapidly decreased each calendar year and stabilized at 1% after 2013. Although the risk of developing TB decreased with year of ART initiation in univariable analysis, there was no significant association after adjusting for sex, age and reason for ART eligibility. Conclusions: The decline in TB incidence over calendar years suggests protective effects of early ART initiation. The high TB incidence within the first month of ART highlights the need for more sensitive tools such as X‐ray and GeneXpert to identify patients living with HIV who have clinical and subclinical TB disease at ART initiation.